Oral health promotion in acute hospital setting: a quality improvement programme - Laura Lennox; Grazia Antonacci; Laraib Ahmed; Samuel Rigby; Sophie Coronini-Cronberg (BMJ Open Quality)
Tooth extraction is the most common hospital procedure for children aged 6–10 years in England. Tooth decay is almost entirely preventable and is inequitably distributed across the population: it can cause pain, infection, school absences and undermine overall health status.An oral health programme (OHP) was delivered in a hospital setting, comprising: (1) health promotion activities; (2) targeted supervised toothbrushing (STB) and (3) staff training. Outcomes were measured using three key performance indicators (KPI1: percentage of children/families seeing promotional material; KPI2: number of children receiving STB; KPI3: number of staff trained) and relevant qualitative indicators. Data were collected between November 2019 and August 2021 using surveys and data from the online booking platform.OHP delivery was impacted by COVID-19, with interventions interrupted, reduced, eliminated or delivered differently (eg, in-person training moved online). Despite these challenges, progress against all KPIs was made. 93 posters were deployed across the hospital site, along with animated video 41% (233/565) of families recalled seeing OHP materials across the hospital site (KPI1). 737 children received STB (KPI2), averaging 35 children/month during the active project. Following STB, 96% participants stated they learnt something, and 94% committed to behaviour change. Finally, 73 staff members (KPI3) received oral health training. All people providing feedback (32/32) reported learning something new from the training session, with 84% (27/32) reporting that they would do things differently in the future.Results highlight the importance of flexibility and resilience when delivering QI projects under challenging conditions or unforeseen circumstances. While results suggest that hospital-based OHP is potentially an effective and equitable way to improve patient, family and staff knowledge of good oral health practices, future work is needed to understand if and how patients and staff put into practice the desired behaviour change and what impact this may have on oral health outcomes.